2017
DOI: 10.1371/journal.pone.0172616
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to determine the feasibility of enhancing cognitive abilities in children with sensory processing dysfunction

Abstract: Children with Sensory Processing Dysfunction (SPD) experience incoming information in atypical, distracting ways. Qualitative challenges with attention have been reported in these children, but such difficulties have not been quantified using either behavioral or functional neuroimaging methods. Furthermore, the efficacy of evidence-based cognitive control interventions aimed at enhancing attention in this group has not been tested. Here we present work aimed at characterizing and enhancing attentional abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(100 citation statements)
references
References 56 publications
7
89
2
2
Order By: Relevance
“…Although this study was conducted in healthy adults only, related work demonstrated that populations with physical and intellectual disabilities can benefit from VR in capturing and maintaining attention [61,62]. Thus, the findings presented here have practical implications for assessing attention-related diseases, including sensory processing dysfunction [63], attention deficit hyperactivity disorder [64], and mild impaired cognition [65] in the context of clinical research. Given that previous work [63][64][65] showed the feasibility of using 2D-based attention assessments and interventions for these diseases, we surmise that the use of a more engaging and enjoyable VR-HMD may indeed follow a similar or even better results.…”
Section: Significance For Future Studymentioning
confidence: 89%
“…Although this study was conducted in healthy adults only, related work demonstrated that populations with physical and intellectual disabilities can benefit from VR in capturing and maintaining attention [61,62]. Thus, the findings presented here have practical implications for assessing attention-related diseases, including sensory processing dysfunction [63], attention deficit hyperactivity disorder [64], and mild impaired cognition [65] in the context of clinical research. Given that previous work [63][64][65] showed the feasibility of using 2D-based attention assessments and interventions for these diseases, we surmise that the use of a more engaging and enjoyable VR-HMD may indeed follow a similar or even better results.…”
Section: Significance For Future Studymentioning
confidence: 89%
“…Cognitive trainings, having components of VGs (i.e. adapting the difficulty level based on the performance and instantly providing the feedback) [11], were found to be effective through the individualization of the training (see Table 1). Constant provision of feedback was helpful for self-monitoring of the progress in VGs [12] in that players were able to change their decisions based on the feedback [13].…”
Section: Genres Of Vgsmentioning
confidence: 99%
“…The improvement in cognitive functions despite the individual difference in the extent to which the functions were improved [11] Children SPD (N = 10), children SPD+ADHD (N = 17), TDC(N = 20)…”
Section: Study Participantsmentioning
confidence: 99%
“…Populárnost her spočívá především v jejich zábavním charakteru, který umožňuje zprostředkovávat jedincům relaxaci, odreagování či odpoutání od reality a povinností. Nepochybně jsou prokázané pozitivní vlivy počítačových her na kognitivní funkce člověka (Mahmoudi et al, 2015), rozvoj specifických dovedností (Nowakowski, Makarewicz, 2018) nebo při využití počítačových her jako terapeutického nástroje (Anguera et al, 2017), aj. Při nadměrném hraní se ovšem mohou počítačové hry stát potenciálně rizikovou aktivitou, z níž plynou zásadní negativní vlivy na člověka.…”
Section: Závěrunclassified